Continuity across change? What memory institutions need to learn for the future. Interview with Samantha Lutz - Dixon, Mar (Hamburger Journal für Kulturanthropologie (HJK), 2018)
In addition to digitizing collections, cultural institutions such as museums have embraced social media as a mode of communication and a way of engaging with the audience. Creative practices of reuse such as the crowd-curated social media events #AskACuratorDay, @52museums or #MuseumWeek on Twitter and Instagram have emerged and are trending worldwide. Mar Dixon, a UK-based social media expert and cultural entrepreneur, has become a passionate advocate for a more people-oriented approach to memory practices in Europe and beyond. Looking back over the past years, in this interview she reflects about what lessons memory institutions should learn for the future of cultural heritage design, pleading for a more reflected approach of safeguarding practices that consider social and technological change.